Metabolic syndrome and heart failure: 40 years follow up results of the Seven Countries Study. (3rd October 2022) - Parapid, B; Simic, D V; Stojsic Milosavljevic, A; Ristic, A; Geleijnse, J M; Danchin, N; Blackburn, H; Jacobs, D; Kromhout, D; Adachi, H; Menotti, A; Nissinen, A; et al.
Abstract: Introduction: Metabolic syndrome (Met Sy) as a highly debatable cluster of traditional risk factors is known to promote cardiometabolic-related morbidity and mortality, but its precise mechanisms remain to be determined. Purpose: We sought to determine influence of MetSy on heart failure (HF) morbidity and mortality in the Seven Countries' Study as one of the oldest epidemiological studies. Methods: The Seven Countries Study encompassed 12, 763 participants from 3 continents who were all healthy men of over 40 years at baseline and who underwent regular check ups every 5 years throughout over a 4 decades' span. Morbidity and mortality was adjudicated according to valid ICD and LPH coding. Results: Using the IDF definition of the Metabolic Syndrome, 9, 09% of participants were identified (Figure 1). HF was confirmed in 220 patients (16.4% alive at 40y follow up visit), while 8.2% died of HF as well in the same time-frame (Tables 1 & 2). Presence of MetSy has been shown to significantly influence HF mortality (Figures 2) with lowest survival of 22% for 300 months of follow up for patients with both MetSy and HF (Log rank test=4.405, p<0.0001). Conclusion: Metabolic syndrome treatment remains in the realm of risk factors' control that now we know influence both ischemic heart disease and heart failure of other origins. Historically, just emerging biomarkers' and targeted imaging weren't available to determine such at the time of HF diagnosis. Also, the sample consisted of men only, mainly Caucasian and a modest proportion of Asian and African-American now known to carry ethnic-specific burden of cardiovascular disease. All of the above, emphasizes the importance of more diversity, equity and inclusion-dedicated long term both observational, as well as interventional research. Funding Acknowledgement: Type of funding sources: None.